Impact of pandemics on primary care: changes in general practitioner antidepressant prescriptions and mental health referrals during lockdowns in England, UK - Fu, Y.; Tang, E.Y.H.; Yu, G. (Public health (London), 2024)
In recent times, the world has witnessed unprecedented challenges, with the COVID-19 pandemic being a major disruptor to various aspects of daily life. This article delves into the profound impact of pandemics on primary care, specifically focussing on changes in antidepressant prescriptions and mental health referrals before, during, and after lockdowns in England, UK. In this retrospective study, we used anonymised individual-level electronic health record data from general practitioner (GP) practices in the North of England, UK. We applied a negative binomial-logit hurdle model and a multinominal logit regression model to assess the impact on antidepressant prescriptions and GP referral types, respectively. The initiation of antidepressant prescriptions showed a notable decrease during and post lockdowns, with a minor uptick in ongoing antidepressant prescriptions during the lockdown periods. Over the course of lockdowns and beyond, there was a growing trend of patients being referred to social prescribing interventions. Notably, individuals from ethnic minorities were more inclined to receive fewer medical treatments and more social prescribing interventions. The increase in antidepressant prescriptions during the pandemic-related lockdowns was expected due to these challenging circumstances. Reduced referrals to secondary mental health services occurred as online counselling services were deemed inappropriate by some doctors, and patients were hesitant to seek face-to-face help. Notably, there was a rise in social prescribing referrals, emerging as a valuable resource for psychological support amid heightened mental health strain. Additionally, ethnic minority patients were less likely to receive medical treatments but more likely to be referred to social prescribing services. Despite the inevitable negative impacts of the COVID-19 pandemic, these findings highlight the active role of non-clinical support in a social model of health, addressing unmet needs and reducing barriers to mental health care for certain groups.